2021
DOI: 10.1111/1365-2435.13828
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal plant‐mediated antagonism between a legume plant virus and soil rhizobia

Abstract: 1. Beneficial plant-associated soil microbes can promote plant tolerance to stress and promote nutrient uptake. Yet, the benefits of microbes for plant health can be altered by above-ground stressors like herbivores and pathogens. However, few studies have assessed reciprocal plant-mediated interactions between beneficial soil microbes and multiple above-ground stressors.2. We assessed if soil rhizobia influenced complex interactions among pea host plants, a vector herbivore (aphids) and a plant virus (Pea ena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…We observed plants attacked by S. lineatus had fewer nodules and lower nodule biomass than controls, suggesting antagonistic effects of S. lineatus on legume-rhizobia symbiosis. Previous studies have also shown that outbreaks of S. lineatus can promote the spread of aphid-borne viruses that also impede the function of rhizobia (Chisholm et al, 2019;Basu et al, 2021a); thus, we have shown that S. lineatus may negatively affect plant-rhizobia symbiosis through multiple indirect pathways.…”
Section: Discussionsupporting
confidence: 55%
“…We observed plants attacked by S. lineatus had fewer nodules and lower nodule biomass than controls, suggesting antagonistic effects of S. lineatus on legume-rhizobia symbiosis. Previous studies have also shown that outbreaks of S. lineatus can promote the spread of aphid-borne viruses that also impede the function of rhizobia (Chisholm et al, 2019;Basu et al, 2021a); thus, we have shown that S. lineatus may negatively affect plant-rhizobia symbiosis through multiple indirect pathways.…”
Section: Discussionsupporting
confidence: 55%
“…Lipoxygenase 2 ( LOX2 ) works upstream of jasmonic acid biosynthesis, a phytohormone hormone used in defense against herbivore pests [ 29 , 30 ]. Similarly, 1-aminocyclopropane-1-carboxylic acid synthases 2 ( ACS2 ) is associated with ethylene synthesis [ 31 , 32 ], and Aldehyde oxidase 3 ( AO3 ) is associated with abscisic acid synthesis [ 33 , 34 ]. Besides ABA biosynthesis, AO3 is also involved in the production of reactive oxygen species (ROS) which, together with abscisic acid, provides resistance against pathogen infection [ 35 ].…”
Section: Methodsmentioning
confidence: 99%
“…Rhizobia can improve plant growth through N 2 fixation and the availability of nutrients and minerals. Similarly, Rhizobia have shown to increase plant growth via the secretion of secondary metabolites of alkaloids and flavonoids that improve plant defense against pathogens (Basu et al, 2021). Earlier studies stated that Rhizobia could stimulate auto defenses in legumes via hormone signaling and start programmed cell death in pathogens (Dodds and Rathjen, 2010;Kumar et al, 2011).…”
Section: Introductionmentioning
confidence: 99%